2014
DOI: 10.1073/pnas.1402468111
|View full text |Cite
|
Sign up to set email alerts
|

Androgens alter T-cell immunity by inhibiting T-helper 1 differentiation

Abstract: The hormonal milieu influences immune tolerance and the immune response against viruses and cancer, but the direct effect of androgens on cellular immunity remains largely uncharacterized. We therefore sought to evaluate the effect of androgens on murine and human T cells in vivo and in vitro. We found that murine androgen deprivation in vivo elicited RNA expression patterns conducive to IFN signaling and T-cell differentiation. Interrogation of mechanism showed that testosterone regulates T-helper 1 (Th1) dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
196
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(213 citation statements)
references
References 30 publications
10
196
2
5
Order By: Relevance
“…It has been suggested that sex differences in Th1 responses arise because of the higher IL-12 production by APC and enhanced T cell responsiveness to this cytokine in females (11,12). We previously observed that even in the absence of IL-12, male CD4 + T cells have a lower intrinsic ability than female CD4 + T cells to produce IFN-g, which associated with higher expression of PPARa (6,7).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been suggested that sex differences in Th1 responses arise because of the higher IL-12 production by APC and enhanced T cell responsiveness to this cytokine in females (11,12). We previously observed that even in the absence of IL-12, male CD4 + T cells have a lower intrinsic ability than female CD4 + T cells to produce IFN-g, which associated with higher expression of PPARa (6,7).…”
Section: Discussionmentioning
confidence: 96%
“…This sex difference is thought to underlie why women generate enhanced antiviral (9) and antitumor (10) immune responses, but also have a higher propensity to develop certain autoimmune diseases (8). Past studies have suggested that sex differences in Th1 responses arise because of suppressive effects of androgens at key nodes in the Th1 differentiation pathway including IL-12 production (11) and signaling (12,13) and IFN-g production downstream of Ag stimulation (6,7). Until recently, the molecular players involved in this androgen-dependent regulation were not known.…”
mentioning
confidence: 99%
“…Consistent with this, a few TFs were increased by STAT6 and associated with suppressive processes in Th1, Th17, or iTreg cells. For instance, AR inhibits IL12 signaling and Th1 cell differentiation by up-regulating Ptpn1 (Kissick et al, 2014), STAT3 activation and HIF1α inhibit iTreg cell differentiation (Laurence et al, 2012;Palazon et al, 2014), and ETV6 is known as a repressor in Th17 cells (Ciofani et al, 2012). However, STAT3 can also induce Th17 cell differentiation (Zhu and Paul, 2010) and promote Th2 cell differentiation together with IL6 (Stritesky et al, 2011).…”
Section: Th2 Cell-specific Tfs Are Positively Regulated By Stat6 Andmentioning
confidence: 99%
“…The increase of CD8 + cells is beneficial for the constant growth of a tumor (18). When the tumor evades the immune system, CD4 + CD25 + Treg cells restrain the activation and proliferation of CD4 + cells by excreting IL-6 and IL-7 cell factors and inducing the activation of signal transducer and activator of transcription 4.…”
Section: Discussionmentioning
confidence: 99%